Cerebral Venous Sinus Thrombosis in Women: Subgroup Analysis of the VENOST Study - MİDİ, İPEK (HINDAWI LTD, 2020)
Background. Early diagnosis of cerebral venous sinus thrombosis (CVST) associated with reproductive health-related risk factors (RHRF) including pregnancy, puerperium, and oral contraceptive (OC) use can prevent severe neurological sequelae; thus, the symptoms must be documented in detail for each group.Methods. Out of 1144 patients with CVST, a total of 777 women were enrolled from a multicenter for the study of cerebral venous sinus thrombosis (VENOST). Demographic, biochemical, clinical, and radiological aspects were compared for 324 cases with RHRF and 453 cases without RHRF.Results. The mean age of the RHRF (-) group (43.2 +/- 13 years) was significantly higher than of the RHRF (+) group (34 +/- 9years). A previous history of deep venous thrombosis (3%), isolated cavernous sinus involvement (1%), cranial neuropathy (13%), comorbid malignancy (7%), and its disability scores after 12 months (9%) were significantly higher in the RHRF (-) group. The RHRF (+) group consisted of 44% cases of puerperium, 33% cases of OC users and 23% of pregnant women. The mean age was found to be higher in OC users (38 +/- 9years). A previous history of deep venous thrombosis was slightly higher in the pregnancy subgroup (4%). Epileptic seizures were more common in the puerperium group (44%).Conclusion. The results of our study indicate that the risk of CSVT increases parallel to age, OC use, and puerperium period. In addition, when considering the frequency of findings and symptoms, epileptic seizures in the puerperium subgroup of the RHRF (+) group and malignancies in the RHRF (-) group may accompany the CSVT. In daily practice, predicting these risks for the CSVT and early recognition of the symptoms will provide significant benefits to patients.
Keywords: POSTPARTUM PERIOD; PREGNANCY; RISK; THROMBOEMBOLISM; STROKE; PUERPERIUM; VEIN